Pembelajaran daring materi daur ulang pada siswa kelas VI SDN 009 Cikadut Bandung dengan menggunakan metode project based learning (PjBL) - Samsudin, Samsudin; Kuswendi, Uus; Pratama, D. Fadly (IKIP Siliwangi, 2025)
This study aims to examine the learning of recycled materials in grade VI students with a contextual method using the online-based Project Based Learning (PjBL) method. The research method used is descriptive qualitative. The subjects in this study were students of class VI SDN 009 Cikadut Bandung City with a total of 28 students. The instruments used are teacher and student observation sheets, test questions, and teacher and student interview questionnaires. The results showed that there was an increase in the quality of learning when the PjBL method was applied. This is indicated by the average value of understanding the science class of 81.07 which is classified in the good category, the highest score of students is 100 and the lowest value is 60. Student learning mastery shows 86.0% of students getting scores above the minimum completeness criteria and 14.0% still gets a score below the minimum completeness criteria value